COVID 19 - Impact on Teaching & Learning :The Gauteng Province Experience - Ntsobi, Mfanelo Patrick; Costa, King (My University, 2022)
In line with massive and complex problems faced by all organisations across the world, COVID-19 outbreak had a severe and disruptive impact in Gauteng provincial public schools. Its effect of forced many institutions to rethink their delivery models. The Gauteng Department of Education (GDE) was compelled to adjust to the new normal to prevent disruption to teaching and learning by unlocking efficiencies emanating from the existing ICT, multi-media as well as broadcasting resources. This presentation presents a rational for rapid intervention and shares on experiences encountered during such an intervention
Keywords: COVID-19; Gauteng Department of Education; ICT; Learning; Teaching